Repurposing Cryptosporidium Inosine 5′-Monophosphate Dehydrogenase Inhibitors as Potential Antibacterial Agents - Mandapati, Kavitha (American Chemical Society, 2014)
[Image: see text] Inosine 5′-monophosphate dehydrogenase (IMPDH) catalyzes the pivotal step in guanine nucleotide biosynthesis. IMPDH is a target for immunosuppressive, antiviral, and anticancer drugs, but, as of yet, has not been exploited for antimicrobial therapy. We have previously reported potent inhibitors of IMPDH from the protozoan parasite Cryptosporidium parvum (CpIMPDH). Many pathogenic bacteria, including Bacillus anthracis, Staphylococcus aureus, and Listeria monocytogenes, contain IMPDHs that should also be inhibited by these compounds. Herein, we present the structure–activity relationships for the inhibition of B. anthracis IMPDH (BaIMPDH) and antibacterial activity of 140 compounds from five structurally distinct compound series. Many potent inhibitors of BaIMPDH were identified (78% with IC(50) ≤ 1 μM). Four compounds had minimum inhibitory concentrations (MIC) of less than 2 μM against B. anthracis Sterne 770. These compounds also displayed antibacterial activity against S. aureus and L. monocytogenes.